THE TEACHERS' CLINIC. - Kaulback, Frank S.; Carmichael, Vernal H.; Fordon, John V.; Allyn, Robert G.; Wright, Howard W. (The Accounting Review, 1951)
Abstract In the study of standard costs, the learner usually has difficulty in determining variances in the accounting for the elements of cost and in setting up entries to record these variances. Generally, less difficulty is encountered in computing and recording variances for direct materials and direct labor, where variances are usually considered to arise from two sources, price variations and quantity variations, than is encountered in computing and recording variances for manufacturing expenses, where variances are usually considered to arise from three sources, budget excess variation, idle capacity variation, and efficiency variation. This discussion will disregard the problems arising out of the handling of variances for direct materials and direct labor, it will present a method which has been used successfully by students in learning to determine and to record the three variances that arise in the handling of the manufacturing expenses. Since manufacturing expenses are entered at an applied rate, a difference will usually exist between the actual and the applied expenses at the end of the period. This difference is classified as over-or under-applied manufacturing expenses and is, in reality, a price variation.